2018
DOI: 10.1002/chem.201705381
|View full text |Cite
|
Sign up to set email alerts
|

From Carboxytelomerization of 1,3‐Butadiene to Linear α,ω‐C10‐Diester Combinatoric Approaches for an Efficient Synthetic Route

Abstract: Two novel reaction pathways were tested to synthesize the linear α,ω-C -diester exclusively from three basic reagents: 1,3-butadiene, carbon monoxide and methanol. Therefore, carboxytelomerization of 1,3-butadiene and methanol was merged with methoxycarbonylation in two different ways to obtain highly linear C -diester. Through a palladium-based and -assisted tandem catalytic system, 22 % yield of the desired C -diester was obtained without isolating the intermediates. Subsequently, the limitations of the nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
(56 reference statements)
0
13
0
1
Order By: Relevance
“…The catalytic system needed to be modified to Pd/P(O‐ i ‐Pr) 3 without pyridine for the assisted tandem‐catalyzed reaction. Acid treatment after the first step still leads to a 22% yield . This reaction can also be carried out using more complex alcohols, for example lignin‐type phenols or even Kraft‐Lignin .…”
Section: Nucleophilesmentioning
confidence: 99%
“…The catalytic system needed to be modified to Pd/P(O‐ i ‐Pr) 3 without pyridine for the assisted tandem‐catalyzed reaction. Acid treatment after the first step still leads to a 22% yield . This reaction can also be carried out using more complex alcohols, for example lignin‐type phenols or even Kraft‐Lignin .…”
Section: Nucleophilesmentioning
confidence: 99%
“…[6] This carbonylative version of the telomerizationreaction [7] encompasses severala dvantagess uch as high atom-economy and the use of industrially accessible reactants (e.g.,b utadiene, CO, alcohols). [11] We recently reported that the reaction can be ef-The palladium catalyzedc arboxytelomerization reactiono fa lcohols with butadiene allows for efficient and atom-economical access to unsaturated alkyl nona-3,8-dienoate esters. [8] Moreover, the butadiene coupling reactions advantageously lead to the formation of two unsaturations and thus open the way to further functionalization.…”
Section: Introductionmentioning
confidence: 99%
“…In the first reaction step, the C9‐monoester as intermediate was quantitatively generated by an optimized palladium‐catalyzed carboxytelomerization ( vide infra for more details on carboxytelomerization). Subsequently, the monoester was isolated by distillation and converted to the C 10 ‐diester in 84 % yield by sequential methoxycarbonylation …”
Section: C4 Moleculesmentioning
confidence: 99%
“…Recently, we have shown that an excess of 1,3‐butadiene increases the stability of the catalyst resulting in quantitative yields of the target product. Moreover, we established a reaction protocol for the synthesis of α,ω ‐diesters as polymer precursors by using a merger of carboxytelomerization and subsequent methoxycarbonylation yielding in 86 % of the linear C 10 ‐diester …”
Section: C4 Moleculesmentioning
confidence: 99%